2020
DOI: 10.15575/call.v1i1.8806
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Prepositional Phrase in Novel ‘The Perfect Nany’ Written by Leila Slimani

Abstract: Prepositional Phrase is the part of preposition and absolutely it is the part of grammar too. It has rules and deregulations that must be obeyed. Without a correct replacement of preposition, the meaning of the sentence can make the people confused. Hence, the research questions of this research are: 1) What are the positions of prepositions phrase of sentences found in Novel The Perfect Nany written by Leila Slimani?. 2) What are the patterns of tree diagram for a prepositional phrase of sentences found in No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Hence, one of the main roles of the prepositional phrase is the adverbial function. The study conducted by Rahmanita et al (2019) on the prepositional phrases employed in the novel 'The Perfect Nanny', to illustrate, has revealed that most prepositional phrases have an adverbial function. The major of their data is prepositional phrases representing the places of events.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one of the main roles of the prepositional phrase is the adverbial function. The study conducted by Rahmanita et al (2019) on the prepositional phrases employed in the novel 'The Perfect Nanny', to illustrate, has revealed that most prepositional phrases have an adverbial function. The major of their data is prepositional phrases representing the places of events.…”
Section: Introductionmentioning
confidence: 99%